Total Haemocytes of Pacific White Shrimp (Litopenaeus vannamei) cultured at salinity of 10 ppt in various stocking density - Febriani, Dian; Marlina, Eulis; Oktaviana, Adni (Airlangga University, 2018)
This study aimed to determine total haemocytes and survival rate of pacific white shrimp cultured at 10 ppt in various stocking density. This study consisted of three treatments with three replicates. The shrimp was cultured at salinity of 10 ppt with different stocking densities: 150 shrimps/m2 (A), 200 shrimps/m2 (B), and 250 shrimps/m2 (C). The result showed that different stocking density affected significantly on the growth performance but gave no effect on the survival and the total of shrimp haemocytes. This study was conducted for five weeks. The best growth performance was seen in the treatment with stocking density of 150 shrimps/m2.Â Keywords: Pacific White Shrimp, Salinity, Stocking density, Total Haemocytes, Survival rate.